The structured oral examination in clinical anaesthesia practice examination papers - Mendonca, Cyprian; Hillermann, Carl; James, Josephine; Kumar, GS Anil (Tfm Pub., 2009)
This book comprises structured questions and answers that closely simulate the structured oral examination (SOE) format of The Royal College of Anaesthetists' final FRCA examination. The style of exam questions has changed over the years and this book matches the most recent changes in this updated exam. It consists of ten sets (chapters) of complete SOE papers.